THEORETICAL UNDERSTANDINGS OF THE CONCEPT OF A ‘PUBLIC SERVANT’: TOWARDS A COMMON DEFINITION - Vukašinović Radojičić, Zorica; Rabrenović, Aleksandra (NBP. Nauka, bezbednosti, policija, 2020)
The public law theorists have been attempting to determine the meaning of the concept of ‘public servant’ on the basis of various criteria. The existing theoretical views often reflect the dynamics of administrative development of individual countries, which directly affects the status and the role of a public servant. Given the lack of a ‘universal definition’, the objective of this paper is to point to the diverse theoretical definitions of the notion of the public servants, which are often associated with the role and characteristics of an individual country’s public administration, legal tradition, and political and social system. Notwithstanding the existing theoretical differences, the paper also aims to establish the common and essential elements of the concept of a public servant, which transcend the national differences. Although the theoretical concept of the public servants offered by legal science often relies on a definition of positive law, the divergences of scientific opinions keep shaping the normative reality as well.
Keywords: public servant, public administration, general interest, theoretical understanding.